2019
DOI: 10.3390/medicina55080453
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Rotator Cuff Tears: A Systematic Review

Abstract: Background and Objectives: Sleep disorders are one of the most common complaints of patients with rotator cuff (RC) tears. However, potential correlations between the treatment of RC tears and the causal factors of sleep disorders are still under discussion. The aim of this review is to evaluate quality of sleep in patients before and after surgery for RC tears and to identify which factors affected patients’ sleep. Materials and Methods: A systematic review was conducted. To provide high quality of the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…Like GH instability, impingement affects the optimal relation between glenoid alignment and the muscle length-tension relationship during arm elevation, with a greater loss of shoulder function [14,15,74]. Displaced clavicular fractures make more common the development of painful SD, and they negatively affect clinical outcomes in comparison to subjects without SD [75,76]. Even if not all clavicular fractures are related to altered shoulder motion, SD is present in the long-term after total claviculectomy [77,78].…”
Section: Causes and Effects Of Sdmentioning
confidence: 99%
“…Like GH instability, impingement affects the optimal relation between glenoid alignment and the muscle length-tension relationship during arm elevation, with a greater loss of shoulder function [14,15,74]. Displaced clavicular fractures make more common the development of painful SD, and they negatively affect clinical outcomes in comparison to subjects without SD [75,76]. Even if not all clavicular fractures are related to altered shoulder motion, SD is present in the long-term after total claviculectomy [77,78].…”
Section: Causes and Effects Of Sdmentioning
confidence: 99%
“…Indeed, not only type of injury, but also several parameters, such as tear size and location [35], surgical technique [36][37][38][39], and concomitant pathologies [21,30,40], may influence the recovery of shoulder function [24,41]. Therefore, only an individualized and supervised rehabilitation program can consider all patient-and surgical-based variables on the basis of which specific exercise programs could be designed [13,39]. However, Hayes et al showed comparable outcomes in patients who had undergone individualized, supervised rehabilitation, and patients who had performed standard unsupervised exercises at home [24].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sleep disorders are among the most frequent complaints of patients with RC tears. Recent studies highlighted the impact that other human variables, such as sleep quality, patient expectation, cognitive, affective psychologic factors or distress, and socioeconomic status may have on the clinical results of RC tears [13,[43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual differences in 3D AHD between the standing and supine positions also varied widely, by up to 4.9 mm, suggesting that the alignment changes in the glenohumeral joint between positions varies between individuals. In cases of rotator cuff tear, the patients often suffer from pain at night and sleep disturbance when lying in the supine position 19 ; therefore, Railhac et al 20 stated that measuring AHD in the supine position is useful in detecting a rotator cuff tear. Different positions can change the subacromial pressure, 21,22 and the narrowing of the AHD in the supine position might increase pain.…”
Section: Discussionmentioning
confidence: 99%